Uma experiência didática com os alunos da educação básica na abordagem dos problemas de coesão na escrita - Jesus, Josineide Oliveira de (2017)
This paper presents the development, the analysis and the results of an investigation with the opinion article genre, through a sequence of classes whose general objective was to investigate the use of cohesive mechanisms in the opinion article by eighth grade students of an elementary school in the municipality of Santa Rita, Paraíba. In the specific objectives, this paper aimed to categorize the nature of occurrences according to the competences: precarious articulation, reasonable articulation and good articulation and present a sequence of activities for a second version of the text through reflection and rewriting. About our research, it is qualitative in nature, with a descriptive-interpretive character that has been configured as an action research. As a theoretical basis, we take as reference works developed by scholars such as Perelman (2005), Bakhtin (2011), Marcuschi (2008), Antunes (2003, 2005), Koch (2007, 2008, 2011, 2015), Geraldi (2011), among others who helped us in this investigation. In the analysis of the 23 texts that composed the corpus, we identified many problems of use of cohesive elements, however, we also found some that used these mechanisms adequately. Although our focus was on cohesion, we could not close the eyes to other problems such as productions that used the theme in a vague way, texts without paragraphs and without punctuation. We believe that these elements are also important for the construction of textuality. Thus, after all this process and the problems that were verified, we start with the proposal of elaboration of activities that, in the future, can be consulted and sent to the rewriting, because we believe that a second version of productions can cause texts with less errors. This is by means of a sequence of activities that contemplate all elements belonging to the genre of opinion.